Synthesis of Some New 2,3/2,4-Disubstituted-1,2,4-Triazino [5,6-b] Indoles - Abdel-Rahman, R.M.; El-Gendy, Z.; M. Fawzy, M. (Asian Journal of Chemistry, 2010)
A number of some new 2,3/2,4-disubstituted-1,2,4-triazino [5,6-b] indoles have been synthesized, the former by the reaction of 3-hydrazone-indol-2(H)one(I), 3-(N-aroyl-hydrazone)-indol-2(H)one(II), 2-arylamino-3-hydrazone-indoles(V) and or 2,3-dihydrazone-1H-indole(VIII) with ammonium acetate, urea, thiourea, ethyl chloroformate and 1,1-dichloroacetic acid. All the new compounds have been characterized by their IR, UV and PMR spectral data.